Incorrect interpretation of the law by the court - S. A. Belov; M. A. Revazov (Правоприменение)
The subject of this study is the main trends that have developed in judicial practice related to the assessment of the correctness of the interpretation of the norms of law by the court. The purpose of the study was to identify the main approaches used by law enforcement agencies, primarily courts, in assessing the possible existence of an error in the interpretation of the applied law by a lower court.General scientific and special methods of scientific cognition were used in the research. Among them are analysis, synthesis, deduction, induction, the systematic method, the hermeneutical method and the legal-dogmatic approach. In particular, published court decisions were analyzed, scientific literature and current legislation were studied, after which conclusions were drawn about the state of law enforcement practice and the prevailing trends when considering by higher courts the issue of a possible error in the interpretation of the law committed by a lower court.The main content of the article is the results of the analysis of judicial practice, the purpose of which was to identify the main trends in judicial practice related to the assessment of the correctness of the interpretation of the norms of law by the court. The practice of applying the provisions of the procedural codes of the Russian Federation, providing for the consequences of a misinterpretation of the provisions of normative acts by the court, is considered. As a result of the conducted research, the main problems that courts face when assessing the correctness of the interpretation given by their colleagues from the lower court were identified. During the analysis, special attention was paid to such aspects as the causes of erroneous interpretation, ways to detect and eliminate the identified error, and the consequences of making an error.Based on the results obtained, conclusions were formulated, among which it is worth noting that judicial errors in the interpretation of normative acts are quite common. At the same time, procedural legislation regulates such situations in different ways in different types of legal proceedings. Having discovered a judicial error in interpretation, the higher court most often does not indicate specific norms that have been misinterpreted, but offers its own solution to the dispute. The errors of the courts in the qualification of those mistakes made by the lower courts were also noted.